The effect of audit committee role and sharia supervisory board role on financial reporting quality at Islamic banks in Indonesia - Rini Rini (Universitas Hayam Wuruk Perbanas, 2014)
This research examines the effect of audit committee role and sharia supervisory board role on financial reporting quality. The data is provided from 33 Islamic banks in Indonesia that were taken by questionnaire from 173 employees (head of group, head of division, and internal auditor), audit committee members, and sharia supervisory board members. The questionnaire consisted of 51 questions. Research instrument contains 15 questions about audit committee role, with two dimensions (role related financial reporting quality and role related internal control); 12 questions about sharia supervisory board role, with two dimensions (control over process of new product development and control over bank activity); and 24 questions on financial reporting quality, with eight dimensions (timeliness, verifiability, completeness, representation faithfulness, neutrality, comparability, consistency and clarity). Data analysis used multiple regressions. The result of this research showed that audit committee role and sharia supervisory board role influenced financial reporting quality simultaneously and partially.